Improved hatchery-rearing techniques for juvenile production of blue swimming crab, Portunus pelagicus (Linnaeus, 1758) - Mhd, Ikhwanuddin; Juariah Hafsya, Mansor; Abol-Munafi, Ambok Bolong; Shabdin, Mohd Long (Blackwell Publishing Ltd, 2012)
The effects of tank colour, larval stocking density, antibiotic administration and water exchange on survival and moulting of blue swimming crab, Portunus pelagicus, were determined. Circular 4-m3 experimental larval-rearing tanks were used in triplicate for all treatments. White, dark grey, blue and brown were tested as tank background colours. The stocking densities tested were 10, 20, 40, 60, 80 and 100 larvae L 1. The effect of oxytetracycline was estimated by comparing a treatment with oxytetracycline to a treatment without oxytetracycline administration. The daily water exchange rates tested were 0%, 25%, 50% and 100% of the tank volume. In all treatments, the larvae were fed with Artemia nauplii, rotifers and encapsulated Spirulina. The highest percentage survival was observed in the dark-grey tanks when the stocking density of larvae was 20 larvae L 1. No larva reached the juvenile crab size in white tanks. No significant difference in survival was found between treated and non-treated larvae with oxytetracycline when the daily water exchange rate was more than 50%.